Sustainable Tourism During Covid-19: Literature Review and Research Agenda - Punit Moris Ekka; Balamurugan Annamalai (ASEAN Journal on Hospitality and Tourism, 2022)
The work systematically reviews the articles published on sustainable tourism during the COVID-19 pandemic. The paper focuses on the current state of knowledge on sustainable tourism, identifies the relevant opportunities for successful implementation and development of sustainability in the tourism industry and gives future directions. Scopus and Web of Science databases were searched, and 184 papers were identified from 2020-to 2021. Each article was evaluated for the study's objective, the data collection steps, the data synthesis process, and the quality measures. The systematic review findings show an increasing interest in research on sustainable tourism adoption post-COVID-19 pandemic in the tourism industry. This is the very first article, which synthesises the published literature on sustainable tourism during COVID-19 pandemic, through Systematic Literature Review method. Our findings indicate that the applications of sustainability in tourism have been focused on all the tourism industry stakeholders. The study will be helpful to predict the extent of current and potential future pandemic effects on the tourism industry. It will also be beneficial for practitioners and policymakers to design new policies aimed at operational sustainability and capacity building of the tourism industry as an active recovery policy for counter-attacking the impact of COVID-19 on tourism.